Gelatin from Jerbung Shrimp Shells (Fenneropenaeus marguiensis de Man) Using Three Types of Solvent: Acetic Acid, Phosphoric Acid, and Sulfuric Acid - Sjamsiah, Sjamsiah; Firnanelty, Firnanelty; Manesa, Sri Haerani Dg; Cahyani, Andi Imas; Rahmawati, Sari (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2024)
Gelatin is a type of protein consisting of amino acids produced through the hydrolysis of collagen. One natural source that can be used as a raw material for making gelatin is the shrimp shell. This study aims to determine the characteristics of gelatin made from Jerbung shrimp shells (Fenneropenaeus marguensis de Man) using three types of acid solvents, namely, acetic acid, phosphoric acid, and sulfuric acid. The hydrolysis process by soaking with acid solvent was carried out with varying concentrations of 1%, 3% and 6%. The results of the analysis of the physical characteristics of gelatin with acetic acid, sulfuric acid and phosphoric acid were suitable for SNI. The pH values ranged from 4.5–6.5, the water content was less than 16%, the ash content was 3.25%, the viscosity ranged from 1.5–7 cP, and the gel strength ranged from 50–300 blooms. The FTIR data of gelatin synthesized from 3 types of acids revealed typical absorption peaks, such as N–H and O–H functional groups at wavenumbers of 3600–3400 cm-1, C–H groups 3000–2840 cm-1, and C=O groups at wavenumbers of 1800–1650 cm-1. These results indicate that Jerbung shrimp shells have potential as alternative raw materials for making gelatin.